KORELASI ANTARA GOI (KOSA KATA) PADA KEMAMPUAN DOKKAI (MEMBACA) MAHASISWA PROGRAM STUDI SASTRA JEPANG UNIVERSITAS BRAWIJAYA - Cahyono, Agus Budi (Universitas Negeri Surabaya, 2016)
The ability to read is the most important skill in learning a foreign language. Reading begins with simple reading passage through short message or reading long-form articles or scientific papers. Goi (vocabulary) are not taught specifically, while goi is the basics before entering dokkai (reading) subjects. From the experience of organizing dokkai course, there appears to be fundamental weakness in the ability to read.This research is quantitative research. This study examines the correlation between students mastery of goi which is reflected in the subject of Argumentative Reading and Writing II. Students of 6th semester 2014/2015 Academic Year Program S1 Japanese Literature Faculty of Humanity Brawijaya University are used as population and sample. Students receive reading and course since 3rd semester. Data collection techniques is done by collecting and assessing in the students mark in Argumentative Reading and Writing II courses as well as making the research instrument in form of a test. The research instrument was made by adjusting the standard JLPT (Japanese Language Proficiency Test) level N3. Data Processing is done by measuring the correlation using Pearson correlation or Product Moment Correlation.